1970
DOI: 10.1037/h0029122
|View full text |Cite
|
Sign up to set email alerts
|

Rats prefer signaled reinforcing brain stimulation to unsignaled ESB.

Abstract: Rats previously shown to be self-stimulators were offered a choice between signaled and unsignaled brain stimulation (ESB) presented on a variable interval (VI) 1-min. schedule in a shuttle box. All animals consistently chose the signaled side whether the interstimulus interval was .5 or 15.5 sec. Given a choice between unsignaled ESB on one side of the shuttle box and no stimuli on the other, three of four animals chose the ESB side; the fourth consistently chose the no-stimulus side. On the basis of the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1
1

Year Published

1970
1970
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 13 publications
1
13
1
1
Order By: Relevance
“…Prokasky (1956) suggested that the preference for predictable over unpredictable food delivery might be due to the enabling of preparatory responses, such as salivation, to occur when food delivery could be anticipated. When electric brain stimulation was used as a reinforcer, it was also found that rats preferred signalled over unsignalled reinforcement (Cantor and LoLordo, 1970). The 'preparatory response' hypothesis, already mentioned in relation to animals' apparent preference for signalled over unsignalled shock (Perkins, 1955(Perkins, , 1968Lockard, 1963) is also applicable to appetitive stimuli.…”
Section: Experimental Studies On the Effects Of Predictability Of Appmentioning
confidence: 85%
“…Prokasky (1956) suggested that the preference for predictable over unpredictable food delivery might be due to the enabling of preparatory responses, such as salivation, to occur when food delivery could be anticipated. When electric brain stimulation was used as a reinforcer, it was also found that rats preferred signalled over unsignalled reinforcement (Cantor and LoLordo, 1970). The 'preparatory response' hypothesis, already mentioned in relation to animals' apparent preference for signalled over unsignalled shock (Perkins, 1955(Perkins, , 1968Lockard, 1963) is also applicable to appetitive stimuli.…”
Section: Experimental Studies On the Effects Of Predictability Of Appmentioning
confidence: 85%
“…Animals and humans permitted to choose between a primary reinforcer preceded by a signal and the same reinforcer unsignaled prefer the signaled reinforcer (Cantor, 1971;Cantor & LoLordo, 1970Furedy & Klajner, 1972;Lewis, Lewin, Muehliesen, & Stoyak, 1974;but see Hershiser & Trapold, 1971). Cantor and LoLordo (1970) administered 0.5-sec trains of electrical stimulation of the brain (ESB) to rats according to a variable-time I-min schedule.…”
Section: Signaled Reinforcementmentioning
confidence: 99%
“…Cantor and LoLordo (1970) administered 0.5-sec trains of electrical stimulation of the brain (ESB) to rats according to a variable-time I-min schedule. The rats were placed in a shuttlebox and provided a choice between receiving ESB preceded by a signal on one side of the chamber and the simultaneous presentation of ESB and signal on the other.…”
Section: Signaled Reinforcementmentioning
confidence: 99%
“…In some cases food pellets were used (Prokasy, 1965), whereas in others liquid reinforcers were used (Hershiser & Trapold, 1971); some have used a commitment procedure (e.g., Lewis et al, 1974), others a noncommitment one (Hershiser & Trapold, 1971).1 The research below assesses 'Two studies have reported a preference for signaled conditions using a noncommitment procedure that conflict with Hershiser and Trapold (1971). These studies used appetitive electrical stimulation of the brain as a reinforcer (Cantor & LoLordo, 1970. However, Cantor (1979) has argued that these conclusions should be questioned since the outcome of these studies may have been affected by an artifact related to the electrode and plug assembly.…”
mentioning
confidence: 99%